Effects of humidification process on thermal performance of floor heating systems: An experimental study - Li, Tianying; Merabtine, Abdelatif; Lachi, Mohammed; Bennacer, Rachid (Building and Environment, 2022)
In dry and cold climates, a cool mist humidifier and a floor heating system are typically used in combination to achieve a pleasant residential environment. In order to investigate the interaction between a humidification process and a heating process, a total of 12 experimental tests were carried out, which included nine experimental groups with a humidification process under the conditions of three indoor temperature set points (21 °C, 23 °C, 25 °C) and three relative humidity set points (45%, 55%, 65%), and three control groups with no humidification process under the conditions of three indoor temperature set points (21 °C, 23 °C, 25 °C). Obtained results show that the indoor environment will reach a new balance in the process of competition between the evaporative cooling and the floor heating, and the floor surface temperature increases when the humidification level rises. The floor overheating problem should be considered while meeting humidification needs at air temperatures of 25 °C or above. The humidification process makes the air temperature distribution more uniform, but increases the energy consumption noticeably. In addition, exergy loss is mainly concentrated in two areas: the building envelope and the floor for the floor heating system. In summary, the set point of RH 45% could meet general health requirements in the case of minimal energy consumption. RH 55% could be selected at below 25 °C for better thermal comfort in particular situations where the energy consumption is acceptable.
Keywords: Energy consumption; Exergy analysis; Floor heating system; Humidification; Thermal comfort